In Custody Based on a Novel by Anita Desai - Merchant, Ismail; Pizer, Larry; Kapoor, Shashi; Azmi, Shabana; Puri, Om (FoxVideo, 1993)
Ismail Merchant makes his directorial debut, after acting as producer for the successful series of James Ivory films. A college teacher takes a freelance assignment to interview an Urdu poet in India and becomes a witness to the death throws of the country's indigenous culture, under assault from ever encroaching Westernization. [www.amazon.co.uk]